Strategic investment planning for the hydrogen economy – A mixed integer non-linear framework for the development and capacity expansion of hydrogen supply chain networks - Pérez-Uresti, Salvador I.; Gallardo, Gustavo; Varvarezos, Dimitrios K. (Computers & chemical engineering, 2023)
•A Mixed-Integer Nonlinear Programming model for the strategic investment planning of large-scale hydrogen economy envelopes is formulated.•Production and carbon capture units are represented using surrogate models derived from rigorous simulation models.•Purity requirements for hydrogen use in transportation as well as the industrial processes are considered as part of the model formulation.•Case study: California's 10-year infrastructure plan achieves a 90 % carbon cut, $6.9B investment, $1.4B NPV. This work presents a novel Mixed-Integer Nonlinear Programming (MINLP) modeling and optimization framework for the investment planning of large-scale hydrogen economy envelopes. The scope of the model includes the design, synthesis, and long-term capacity expansion of hydrogen supply chain networks (HSCN) that include hydrogen production, purification, storage, transportation, and distribution, subject to environmental sustainability considerations. Production and carbon capture units are represented using surrogate models derived from rigorous simulations to capture important process non-linearities. This framework provides an optimal roadmap for the 10-year plan of hydrogen infrastructure development in the state of California, that demonstrates the important trade-offs between investment decisions, economic incentives, and regulatory carbon emissions constraints. It is shown that the development of the hydrogen production and distribution networks can be achieved over a 10-year horizon in an economically profitable way, while achieving a 90 % reduction in carbon emissions and satisfying all state regulatory mandates.